2003
DOI: 10.1016/s0092-8674(03)00771-2
|View full text |Cite
|
Sign up to set email alerts
|

TSH Is a Negative Regulator of Skeletal Remodeling

Abstract: The established function of thyroid stimulating hormone (TSH) is to promote thyroid follicle development and hormone secretion. The osteoporosis associated with hyperthyroidism is traditionally viewed as a secondary consequence of altered thyroid function. We provide evidence for direct effects of TSH on both components of skeletal remodeling, osteoblastic bone formation, and osteoclastic bone resorption, mediated via the TSH receptor (TSHR) found on osteoblast and osteoclast precursors. Even a 50% reduction i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
532
3
14

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 602 publications
(574 citation statements)
references
References 40 publications
25
532
3
14
Order By: Relevance
“…We suggest that vertebrate T cell differentiation and activation are controlled, at least in part, by thyroid axis hormones regardless of the location or origin of the T cells (thymus, lymph node, spleen, or intestine). The findings reported here, as well as those demonstrating a direct role for TSH in bone remodeling [41], add to the growing body of information indicating that TSH is a multidimensional molecule with properties that extend beyond the neuroendocrine system [42]. Three-color staining of small intestinal IELs for expression of TSHR, CD4, and CD8.…”
Section: Discussionsupporting
confidence: 58%
“…We suggest that vertebrate T cell differentiation and activation are controlled, at least in part, by thyroid axis hormones regardless of the location or origin of the T cells (thymus, lymph node, spleen, or intestine). The findings reported here, as well as those demonstrating a direct role for TSH in bone remodeling [41], add to the growing body of information indicating that TSH is a multidimensional molecule with properties that extend beyond the neuroendocrine system [42]. Three-color staining of small intestinal IELs for expression of TSHR, CD4, and CD8.…”
Section: Discussionsupporting
confidence: 58%
“…Also, TSH is reported to have a direct effect on bone turnover through TSHRs on osteoblasts and osteoclasts (37). However, other that the shortening of a few facial bones, the skeletons of OGH-TG mice are normal.…”
Section: Resultsmentioning
confidence: 99%
“…Increasing data showed that the TSHR was also expressed in many nonthyroid tissues, and it might actually play a physiological role in these tissues. 8,9 We recently demonstrated that TSHR was expressed in hepatocytes and that stimulation of cultured liver cells with TSH increased the production of cAMP. 10 These results suggested that the TSHR might play an important role in the regulation of liver function.…”
mentioning
confidence: 99%